MAQASID AL-SYARIâAH: Lit Imtisal wa lkhrÃ£ji al-MukalIaf an IttibÃ£âi al-Hawa - Halim. K., Abd. (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article outlines the study of the existence of Maqasid al-Shariah to be guided, so that man/mukallaf free from the influence of lust. Discussion of the results obtained by the understanding that the existence of maqasid aI-Shariah, is to realize the benefit of earthly life and the hereafter. For this purpose, it should be used as guidelines maslahah (philosophy) life. Maslahah in terdirii on three levels, namely: daruriya,. hãjiah. and tahsiniyah. Daruriyah intent, is everything that should be there for the establishment of a way of life; nourish the soul, religion, intellect, lineage, and treasure. While hajiah, is everything dihajatkan-population to avoid masyaqqah. As is tahsiniyah is take into-use of all appropriate and inappropriate justified by customs as Makarim al-akhlak. In mengimplemtasikan maqasid al-Shariah in life, the human / mukallaf must be free from lust. Human liberation of desire lust, meant that they could be servants in ikhtiyãr (free), does not idtirãr (forced). In this case, the law does not mean it will turn off lust, lust except Him let it work in proportion to benefit for life. Lust potential benefit to a certain extent, but if left unchecked lust mala will appear with destructive properties. In this concept, the charity which instructed all law is always accompanied by the requisite ability (isititaah) for the mukallaf